2016
DOI: 10.1097/qai.0000000000000943
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: A High Rate of β7+ Gut-Homing Lymphocytes in HIV-Infected Immunological Nonresponders is Associated With Poor CD4 T-Cell Recovery During Suppressive HAART

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…Interestingly, α4β7-integrins favor the HIV colonization of GALT and the establishment of mucosal HIV reservoir ( 31 ). In this line, the higher expression of α4β7 in CD4 T-cells recently reported in a different cohort of immunodiscordant subjects under suppressive cART, was correlated with a higher proviral HIV load ( 24 ). Additionally, the expression of OX40 on CD4 T-cells has been associated with a high metabolic activity which is ultimately associated with a higher permissibility to HIV infection ( 32 ), and HP process itself has been also associated with higher amounts of HIV provirus ( 33 ).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Interestingly, α4β7-integrins favor the HIV colonization of GALT and the establishment of mucosal HIV reservoir ( 31 ). In this line, the higher expression of α4β7 in CD4 T-cells recently reported in a different cohort of immunodiscordant subjects under suppressive cART, was correlated with a higher proviral HIV load ( 24 ). Additionally, the expression of OX40 on CD4 T-cells has been associated with a high metabolic activity which is ultimately associated with a higher permissibility to HIV infection ( 32 ), and HP process itself has been also associated with higher amounts of HIV provirus ( 33 ).…”
Section: Discussionmentioning
confidence: 55%
“…It is well-known that immunodiscordant subjects present higher frequencies of Treg ( 21 , 22 ) and Th17 ( 23 , 24 ) after cART initiation. Additionally, we have recently reported that increased frequencies of both Treg and Th17 are already present before cART initiation ( 5 , 6 ) in these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Ϫ cells in vitro (9). This is also supported by studies that demonstrate preferential infection of ␣ 4 ␤ 7 high cells in vivo (10)(11)(12). Because these cells are present at high density in the gut (13) and are highly susceptible to HIV-1 infection, they may facilitate HIV-1 propagation throughout GALT.…”
mentioning
confidence: 75%
“…The frequency of CD4+CCR9+α4β7+ cells featuring a gut-homing phenotype was also significantly impaired in untreated HIV infection and correlated with the HIV RNA load and CD4+ activation. Upon cART introduction, we observed a further contraction of this subset which may be either due to their migration from the peripheral blood to the gut in the course of cART [26] or apoptosis. Although we do not have evidence to prove these hypotheses, given that CD4+CCR9+α4β7+ serve as viral targets [32], our results may point to ongoing infection and damage at mucosal sites even in the course of effective treatment, thus highlighting the role of this population in the pathogenesis of HIV disease within the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the absence of correlation between CD4+CCR9+α4β7+ cells and markers of T-cell activation after the introduction of treatment allow for the speculation that the repopulation of this gut-homing population at mucosal sites may be linked to decreased inflammation as well as the containment of the HIV reservoir [26]. Studies aimed at investigating the precise migration patterns of gut-homing populations and their effects on the structure of the gut barrier are warranted in humans to shed light on their contribution to HIV pathogenesis.…”
Section: Discussionmentioning
confidence: 99%